POLINATOR INSECT COMPOSITION TANAMAN APPLE (Malus sylvestris Mill) IN PONCOKUSUMO VILLAGE, MALANG DISTRICT, EAST JAVA - Frank Leonardo Apituley (Sean Institute, 2023)
The apple tree is one type of tree can not pollinate itself. Apple flowers depend on insect pollinators. This study aims to determine the composition of canopy insects as pollinators of flowers potentially apple and analyze visit patterns, and identify how the local people's perception of insect pollinators. Insect visual observations performed. Measurement of environmental factors (temperature, humidity, and light intensity). Data analysis of insect community structure during seasons of flowering and fruiting gained importance and diversity (Shannon Wienner Index). Pattern and composition of insect pollinators visit is done by comparing the flowering season and fruiting season. Parameters are compared to diversity, abundance and composition. Diversity and abundance compared to the test and ANOVA, whereas compared to IBC composition (Bray Curtis Index). Patterns of insect pollinators of flowers daily visits were analyzed by comparing apples average visits in period I, II, III, IV, and V. Insect pollinators of apples collected in the spring plantation higher at (363 individuals) of the fruit season (151 individuals). Diversity index value of insect pollinators during the flowering season was higher (2.08) than the fruit season (1.27). Abundance of insect pollinators of flowers and fruits of the season significantly P < 0.001. The similarities between insect pollinators of flowers and fruit seasons premises Bray Curtis index of 0.76 for the spring (AC, the hours 07:00 a.m. to 08:15 with a 12:00 to 13:15) and 0.74 for the fruit season (AB, the hours 07:00 a.m. to 8:15 with a 09:00 to 10:15). Analysis of environmental factors of temperature, humidity, and light intensity on the abundance of insect pollinators found a positive correlation with the R-square value of 43.2%.